SmartDryBox: An Eco-Friendly Automatic Clothes Dryer Based on Air Conditioner Waste Heat and IoT - achmadi achmadi; Okto Rosario Nisen Loasana; Aulia Rahman (Universitas Kristen Cipta Wacana, 2026)
Smartdrybox represents an innovative clothing dryer designed to mitigate electrical energy consumption and carbon emissions by harnessing waste heat from air conditioning (AC) systems. Grounded in the 6R framework (Reuse, Reduce, Rethink, Recycle, Repair, and Replace), this system integrates an Internet of Things (IoT) mobile application to facilitate real-time drying monitoring. The primary objective of this development is to present an energy-efficient solution tailored for residential households, boarding houses, and micro-scale laundry enterprises, thereby decreasing reliance on conventional electric dryers. Structurally, the Smartdrybox consists of a cabinet drying enclosure coupled to the AC exhaust outlet via an adjustable duct system. A built-in humidity sensor quantifies the moisture level of the garments, while a diffuser ensures uniform airflow distribution. An integrated microcontroller processes the acquired sensor data and transmits telemetry to the user through a dedicated IoT application. Furthermore, automated notifications are generated upon completion of the drying cycle, with drying durations fully adjustable to meet specific operational requirements. This innovation yields several distinct advantages, including the valorization of AC thermal waste (Reuse), the integration of IoT to optimize temporal efficiency, and a modular design compatible with diverse air conditioning configurations. Additionally, the system ensures fabric preservation across various textile types due to the absence of auxiliary heating elements. By synthesizing the 6R principles, IoT-driven automation, and energy recycling, the Smartdrybox aligns with green technology and smart home paradigms, demonstrating substantial potential for future research and development.